1994
DOI: 10.1177/0305735694222004
|View full text |Cite
|
Sign up to set email alerts
|

Handedness and Musical Ability: A Study of Professional Orchestral Players, Composers, and Choir Members

Abstract: The handedness of three groups of accomplished musicians (623 instrumentalists, 331 composers, and 584 choir members) was assessed using a standard questionnaire (Oldfield, 1971). While the three groups of musicians did not differ from one another, there was evidence of a modest, but significant, increase in the proportion of left-handers and mixed-handers among the musicians when compared with a normal population. It was found, for example, that 12-2% of the male and 11-8% of the female musicians were lefthan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 23 publications
0
24
1
Order By: Relevance
“…The combined rating on these ladders can predict health-related outcomes as well as, or better than, other more objective measures of SES (e.g., Singh-Manoux, Marmot, & Adler, 2005). Given evidence (albeit mixed) for a greater prevalence of lefthandedness in musicians (Aggleton, Kentridge, & Good, 1994), handedness effects on musical ability (e.g., Kopiez, Galley, & Lee, 2006;Jäncke, Schlaug, & Steinmetz, 1997), and handedness effects on cognitive tasks (also with somewhat mixed findings; e.g., Beratis, Rabavilas, Kyprianou, Papadimitriou, & Papageorgiou, 2013;Nettle, 2003;Powell, Kemp, & García-Finaña, 2012), we administered the Edinburgh handedness inventory (Oldfield, 1971). Finally, bilingualism has been found to predict aspects of EF (e.g., Bialystok, Craik, Green, & Gollan, 2009), so we administered the Language Experience and Proficiency Questionnaire (LEAP-Q; Marian et al, 2007): participants were considered bilingual if they reported speaking a second language with a mean self-rated proficiency of at least 5 on a 1 to 10 scale (where 5 is defined as "adequate"), averaged across ratings of ability in second language speaking, understanding, and reading.…”
Section: Other Background and Demographic Measuresmentioning
confidence: 99%
“…The combined rating on these ladders can predict health-related outcomes as well as, or better than, other more objective measures of SES (e.g., Singh-Manoux, Marmot, & Adler, 2005). Given evidence (albeit mixed) for a greater prevalence of lefthandedness in musicians (Aggleton, Kentridge, & Good, 1994), handedness effects on musical ability (e.g., Kopiez, Galley, & Lee, 2006;Jäncke, Schlaug, & Steinmetz, 1997), and handedness effects on cognitive tasks (also with somewhat mixed findings; e.g., Beratis, Rabavilas, Kyprianou, Papadimitriou, & Papageorgiou, 2013;Nettle, 2003;Powell, Kemp, & García-Finaña, 2012), we administered the Edinburgh handedness inventory (Oldfield, 1971). Finally, bilingualism has been found to predict aspects of EF (e.g., Bialystok, Craik, Green, & Gollan, 2009), so we administered the Language Experience and Proficiency Questionnaire (LEAP-Q; Marian et al, 2007): participants were considered bilingual if they reported speaking a second language with a mean self-rated proficiency of at least 5 on a 1 to 10 scale (where 5 is defined as "adequate"), averaged across ratings of ability in second language speaking, understanding, and reading.…”
Section: Other Background and Demographic Measuresmentioning
confidence: 99%
“…The proportion of left-handers also appeared to be greater in gifted children (IQO131) than in non-gifted children , but the importance of this effect at the population level remains to be quantified, owing to the low proportion of gifted children. A few studies have considered that left-handers could have special talents that could lead to benefits, such as enhanced musical (Aggleton et al 1994;Kopiez et al 2006) or mathematical capacities (Casey et al 1992;Crow et al 1998), although this last fact seems controversial (Peters 1991). All these advantages may play a significant role in the social status of left-handers.…”
Section: Evolutionary Forces Acting On the Polymorphism Of Handednessmentioning
confidence: 99%
“…Oldfield concluded that no great or widespread difficulty was experienced in reversing the dom inant and nondom inant hands in musical execution as, if this were the case, we would have expected to see a lower prevalence of left-handers am ong musicians. More recently, Aggleton, Kentridge, and Good (1994) have collected responses to the same handedness questionna ire from 1 538 participants from different British orchestras. These authors report an increased prevalence of orchestral m usicians using their left hand for writing (male musicians = 12.5% ; female musicians = 12.6% ) when com paring their frequencies to those of the general popula tion data of Davis and Annett (1994).…”
Section: Prevalence Of Left-handedness In Piano Players In a Music Scmentioning
confidence: 99%